Unemployment benefits and unemployment - Robert Moffitt; Wonsik Ko (IZA World of Labor, 2024)
All developed economies have unemployment benefit programs to protect workers against major income losses during spells of unemployment. By enabling unemployed workers to meet basic consumption needs, the programs protect workers from having to sell their assets or accept jobs below their qualifications. The programs also help stabilize the economy during recessions. If benefits are too generous, however, the programs can lengthen unemployment and raise the unemployment rate. The policy challenge is to protect workers while minimizing undesirable side effects
Keywords: H53; J64; J65; 330; unemployment benefits; unemployment; recessions